Penerapan Model Problem Based Learning Berbantuan Video Animasi untuk Meningkatkan Hasil Belajar Matematika Peserta Didik - Wahyuni, Susi (Postulat : Jurnal Inovasi Pendidikan Matematika, 2022)
This study aims to improve students' mathematics learning outcomes through the application of Problem Based Learning (PBL) assisted by Video Animation. This research includes classroom action research referring to the Kemmis and Taggart models with 2 cycles consisting of planning, action, observation and reflection stages. The research subjects were 32 students of class XI DPIB A at SMK Negeri 2 Trenggalek. The instruments used were observation sheets on the implementation of the Learning Implementation Plan (RPP) and learning outcomes tests in the form of essay questions. The results showed that, 1) the implementation of lesson plans had increased, namely in cycle I at the first meeting of 55 and at the second meeting of 60, then in cycle II, the score increased to 62 at the first meeting and 64 at the second meeting, 2) the average score of students' test results increased, namely in the first cycle of 63,78 and in the second cycle of 80,00. Classical completeness has increased, namely in the first cycle of 62,50% increasing to 84.37% in the second cycle. Thus, it can be concluded that the application of the Problem Based Learning assisted by Video Animation can improve students' mathematics learning outcomes. Keywords: Problem Based Learning, Video Animation, Learning Outcomes.